PELATIHAN PENYUSUNAN LAPORAN KEUANGAN PADA USAHA UMKM TEMPE MURNI BERDASARKAN SAK EMKM - Okta, Oktavie Fresiliasari; Suhardjo, Yohanes; Widyakto, Adhi (Jurusan Akuntansi Politeknik Negeri Sriwijaya Palembang, 2024)
Tempe Murni UMKM is one of the UMKM businesses in Pedurungan District which is engaged in the manufacture and sale of tempeh. This business is known to have not recorded financial transactions properly and correctly. This is indicated by the absence of financial reports regarding the amount of profit or loss, either daily, monthly, or annually. Therefore, this community service activity aims to provide an understanding of accounting in preparing financial reports in accordance with SAK EMKM for UMKM managers. The method used is a qualitative method by means of observation and interviews which produce data in the form of written or spoken words that can be observed from the owner of Tempe Murni UMKM. The results of this community service activity may still have many shortcomings, but basically the output results obtained in this activity are that the owner and employees of Tempe Murni UMKM already understand and are also able to prepare UMKM financial reports. Suggestions for the future, Tempe Murni UMKM must switch to using financial application technology so that the process is easier and does not complicate the preparation of UMKM financial reports based on SAK EMKM.